Osteoclasts and their precursors are present in the induced‐membrane during bone reconstruction using the Masquelet technique. (12th June 2014) - Gouron, Richard; Petit, Laurent; Boudot, Cédric; Six, Isabelle; Brazier, Michel; Kamel, Said; Mentaverri, Romuald
Abstract: In 2000, Masquelet reported a long bone reconstruction technique using an induced membrane formed around a polymethylmethacrylate (PMMA) spacer placed in the defect with appropriate stabilization followed by secondary bone graft after PMMA removal. This reconstruction procedure allows rapid and safe bone reformation for septic, traumatic, neoplastic or congenital bone defects. A rat model of the Masquelet technique was developed to further characterize the biological activities of this induced membrane. Our model allows healing of a critical‐sized femoral defect (8 mm) by means of this procedure over a period of 18 weeks. Comparison of induced membranes obtained 3, 4, 5 and 6 weeks after PMMA insertion indicated that this tissue changes over time. Several mineralization spots and bone cells were observed in contact with the PMMA, when assessed by Alizarin Red, Von Kossa, Alkaline phosphatase and Tartrate‐resistant acid phosphatase staining of the membranes. CTR (calcitonin receptor)‐ and RANK (Receptor Activator of Nuclear factor Kappa B)‐ positive mononuclear cells were detected in the induced membrane, confirming the presence of osteoclasts in this tissue. These cells were observed in a thin, highly cellular layer in the induced membrane in contact with the PMMA. Together, these findings suggest that the membrane is able to promote osteointegration of autologous corticocancellous bone grafts during the Masquelet technique by creating local conditions that may be favourable to graft bone remodelling and osteointegration. Copyright © 2014 John Wiley & Sons, Ltd.